The Kingdom of the Bicycle : What Wuhan Can Learn from Amsterdam - Frame, Gladys; Ardila-Gomez, Arturo; Chen, Yang (Elsevier, 2018)
China used to be called “the Kingdom of the Bicycle,” but this is no longer the case. Bicycle use in China has been marginalized over the past 30 years. In contrast, the Netherlands has seen bicycle use grow since the 1970s. This paper—through a comparative analysis of data from Wuhan and Amsterdam—explores the reasons why the two countries have gone in different directions. Although these cities have different socio-demographics they experienced similar issues. This paper suggests lessons that Wuhan can learn from Amsterdam. However, these are one-way as it is considered that Amsterdam has little to learn from the decline of bicycle use in Wuhan.